A Study of Cheng Yi’s Quiet-Sitting Meditation and Other Contemplative Practices in the Confucian Context - Bin Song (Journal of Contemplative Studies)
This study delves into Cheng Yi’s (程頤, 1033–1107) Ruist (Confucian) contemplative practices, addressing a gap in contemplative studies from a Ruist perspective. As a seminal thinker in the Cheng-Zhu lineage, Cheng Yi developed various practices, including quiet-sitting meditation, beholding, calligraphy, restful sleep, and others. These practices incorporate techniques such as sitting postures, breathing, and calming the mind and emerged during political and social crises, amid diverse interpretations of Ruist classics and the influences of Buddhism and Daoism. Cheng Yi’s contemplative approach emphasizes the integration of the virtues of “reverence” and “righteousness,” focusing on the ontological and empirical dimensions of the human heartmind. His metaphysics highlights the nontemporality of the pattern-principle’s regulatory role, enhancing the pan-contemplative nature of the Ruist lifestyle. Cheng Yi’s approach provides valuable comparative insights for contemporary contemplative studies and guidance for practitioners seeking to balance intellectualism, contemplation, and ethical action. The study offers original translations and comprehensive scholarly analysis of Cheng Yi’s Ruist contemplative practices.